Calcium Oxide Catalyst Based on Quail Eggshell for Biodiesel Synthesis from Waste Palm Oil - Risfidian Mohadi; Abi Sueb; Kiki Anggraini; Aldes Lesbani (Chemistry Department, The University of Brawijaya, 2018)
Calcium oxide decomposed from quail eggshell was used as catalyst for biodiesel synthesis from waste palm oil. Prior to being used, the quail eggshell was decomposed at 600-1100 oC to form calcium oxide and it was characterized by X-Ray measurement, FTIR and SEM spectroscopy to analyze the functional groups and the surface morphology, followed by N2 adsorption desorption methods to determine the surface area. The results of X-Ray analysis powder pattern show that the decomposition of quail eggshell at 900 oC gave calcium oxide that has similar characteristic to the standard CaO from Joint Committee of Powder Diffraction Standard (JCPDS). The FTIR spectrum indicated vibration of calcium oxide from quail eggshell have a similar pattern with the calcium oxide of the standard. The SEM analysis showed that morphology of quail eggshell was changed after decomposition at 900 oC and it have the mesoporous structure. The biodiesel from waste palm oil was synthesized using CaO catalyst from quail eggshell decomposed at 900 oC. The biodiesel product has density of 0.86 g/cm3, viscosity of 5.50 mm2/s, free fatty acid of 0.56 mg/KOH, and iodine number of 60.49 g I2/100g, respectively. All those biodiesel characteristics meet to the biodiesel standard by the Indonesian National Standard (SNI).